Differentiated Learning to Facilitate Students’ Interests in the Content of English Language Learning - Heningjakti, Evanda Pangesti Mahardhika; Surono, Surono (JADEs Journal of Academia in English Education, 2023)
With the new curriculum pushing student-centered learning even further, the differentiated learning supposedly becomes the approach to be utilized. Still, students’ interests were supposed to be made into consideration for the content, strategy, product, and environment, but such a notion remains to be seen. Therefore, this study aims to examine remaining issues and challenges faced by the teacher and students of grade 8 as well as to explore how the differentiated content can facilitate students’ interests. Based on descriptive qualitative in nature, the data were obtained mainly from personal interviews with six grade 8 students of SMPN 12 Yogyakarta, their English teacher, and the vice principal for curriculum affairs, and partly through observation and survey of a class. The findings revealed that there were prevalent issues and challenges in the curriculum, the teaching and learning practices, the materials, and the students’ interests. Then, the differentiated contents could facilitate students’ interests in terms of identifying their interests, grouping them based on their interests, providing relevant topics, presenting the content in various interesting media, and utilizing technology to provide sources of learning